Implementation of Small Sided Games to Improve Passing Skills Football - Indra, Indra Aditiya; Widiastuti, Widiastuti; Hernawan, Hernawan (Journal of Sport Science and Fitness, 2025)
Introduction: This study aims to improve football passing skills among U13 players at Farama Football Club. Objectives: The research was conducted from May to June 2025 at Setu Cipayung Field, East Jakarta, involving 20 participants from Farama FC U13 team. Method: This study employed Action Research methodology with a one-group pre-test post-test design. The instrument used was a passing skills test validated by football ex-perts and specialists. Data analysis utilized descriptive statistics to compare pre-test and post-test results. Result: The pre-test revealed that players achieved 59% passing accuracy with an average score of 71 out of 120. Following eight training sessions imple-menting Small-Sided Games methodology, the post-test demonstrated significant improvement to 88.51% with an average score of 108 out of 120. This 29.51% improvement indicated that the intervention successfully addressed the identified problem. Conclusion: Consequently, the research was completed in one cycle without requiring continu-ation to subsequent cycles. The findings demonstrate that Small-Sided Games effectively improve football passing skills in youth players.